EFEKTIVITAS PENYELENGGARAAN DEKONSENTRASI SEBAGAI WEWENANG GUBERNUR DALAM KEDUDUKAN SEBAGAI WAKIL PEMERINTAH PUSAT DI DAERAH - Bakti Setiawan, Dian; Zahara, Zahara (UNES Law Review, 2022)
Deconcentration is an important element in the administration of the state. Its existence is not only in administrative law order, but also in Constitutional law because - like decentralization - it concerns the foundations and organization of the state. If decentralization gave birth to local government (autonomous region), then deconcentration gave birth to local state government (administrative area). These administrative areas are headed by what is known theoretically as a Prefector. For the Indonesian context, the prefector is held by the governor in such a way that the governor has a dual position, namely as the head of the autonomous region of the province as well as the prefector. The laws governing local government in Indonesia use the term representative of the center in the regions for the designation of prefector. Since the reformation until now, the administration of government from the center to the regions seems to have marginalized deconcentration as the governance structure. There was a strong impression during the reform era that looked at deconcentration as if were the antithesis of democracy. The impression was so strong that deconcentration and administrative areas were no longer included in the post-amendment 1945 Constitution. The deconcentrative authority possessed by the governor to revoke Regency/City Regional Regulations (Perda) that are contrary to higher laws, public interests, and decency, was annulled by the constitutional court in its decision in 2016. Furthermore, budgeting and regulation and formation the apparatus that assists the governor as the central representative in the regions appears to be running slowly. In this way the question arises: is the implementation of deconcentration effective by the governor as the representative of the central government in the regions? To answer this question, research was carried out on the implementation of the deconcentration. The results of the research show that the implementation of the deconcentration has not been effective due to various limitations: limited tools, limited rules, and limited authority